Human Ecological Analysis of the Life of Pi - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2015)
In this article, I have discussed how can we analyze an adventurous and fantasy Novel like “Life of Pi” from human ecological perspective. Knowledge is generated and applied in diverse spatial and temporal contexts, which has varied implication to individuals, households, communities, and human kind as a whole. The implication confines not only to human being would be equally implicate to the surrounding of biotic and abiotic elements. The human ecological knowledge of “Life of Pi” is one of such case. The early life of Mr. Pi and his social educational background had great implication on his later academic life, thinking, acting and feeling as well as for livelihood. How diversity plays a great role in our perception and creates beautify of life around us? The difference between 'knowing how' and 'knowing that' is felt by people of different socio-economic background. Knowing how is more relevant in the context of practical or empirical knowledge. Knowing that is a formal informed knowledge with little connotation of empirical understanding. Combination of both types of knowledge is important in human ecological analysis. In this article I have tried to explore complex connectivity in relation with human being, diverse animal’s world, and landscape relation from human ecological perspective which can be vividly locate in the Novel.